Effects of gestational inflammation on age-related cognitive decline and hippocampal Gdnf-GFRα1 levels in F1 and F2 generations of CD-1 Mice - Bao-Ling Luo; Zhe-Zhe Zhang; Jing Chen; Xue Liu; Yue-Ming Zhang; Qi-Gang Yang; Gui-Hai Chen (BMC Neuroscience, 2023)
Abstract Background It has been reported that age-associated cognitive decline (AACD) accelerated by maternal lipopolysaccharide (LPS) insult during late pregnancy can be transmitted to the second generation in a sex-specificity manner. In turn, recent studies indicated that glial cell line‐derived neurotrophic factor (GDNF) and its cognate receptor (GFRα1) are critical for normal cognitive function. Based on this evidence, we aimed to explore whether Gdnf-GFRα1 expression contributes to cognitive decline in the F1 and F2 generations of mouse dams exposed to lipopolysaccharide (LPS) during late gestation, and to evaluate also the potential interference effect of pro-inflammatory cytokines. Methods During gestational days 15–17, pregnant CD-1 mice (8–10 weeks old) received a daily intraperitoneal injection of LPS (50 μg/kg) or saline (control). In utero LPS-exposed F1 generation mice were selectively mated to produce F2 generation mice. In F1 and F2 mice aged 3 and 15 months, the Morris water maze (MWM) was used to evaluated the spatial learning and memory ability, the western blotting and RT-PCR were used for analyses of hippocampal Gdnf and GFRα1 expression, and ELISA was used to analyse IL-1β, IL-6 and TNF-α levels in serum. Results Middle-aged F1 offspring from LPS-treated mothers exhibited longer swimming latency and distance during the learning phase, lower percentage swimming time and distance in targe quadrant during memory phase, and lower hippocampal levels of Gdnf and GFRα1 gene products compared to age-matched controls. Similarly, the middle-aged F2 offspring from the Parents-LPS group had longer swimming latency and distance in the learning phase, and lower percentage swimming time and distance in memory phase than the F2-CON group. Moreover, the 3-month-old Parents-LPS and 15-month-old Parents- and Father-LPS groups had lower GDNF and GFRα1 protein and mRNAs levels compared to the age-matched F2-CON group. Furthermore, hippocampal levels of Gdnf and GFRα1 were correlated with impaired cognitive performance in the Morris water maze after controlling for circulating pro-inflammatory cytokine levels. Conclusions Our findings indicate that accelerated AACD by maternal LPS exposure can be transmitted across at least two generations through declined Gdnf and GFRα1 expression, mainly via paternal linage.